El Dengue - Jorge R. Rey (EDIS)
ENY-737S, a 5-page illustrated fact sheet by Jorge Rey, is the Spanish language version of ENY-737: What is Dengue? It describes this human disease caused by a virus transmitted by mosquitoes. It describes the viruses, the vectors, the disease and its history. Includes selected references. Published by the UF Department of Entomology and Nematology, April 2007.